The Role of PAI Teachers and the School Environment in Forming the Patient and Forgiveness Character of SMAN 19 Students - Rizky Putra Darmawan; Ika Puspitasari; Moch. Charis Hidayat (FKIP - Universitas Riau, 2026)
Character education is an important aspect of developing students’ moral and spiritual values, particularly in fostering attitudes such as patience and forgiveness within the school environment. This study aims to analyze the role of Islamic Religious Education (PAI) teachers and the school environment in shaping students’ patience and forgiveness characters at SMAN 19 Surabaya, as well as to identify supporting and inhibiting factors in the character-building process. This research employed a qualitative field research approach. Data were collected through observation, interviews, and documentation involving PAI teachers and eleventh-grade students. Data analysis used the Miles and Huberman model, including data collection, data reduction, data display, and conclusion drawing. The findings show that PAI teachers play a central role in developing students’ patience and forgiveness through exemplary behavior, contextual learning strategies, and the habituation of positive attitudes during the learning process. A supportive school environment and religious culture also strengthen the internalization of these character values. However, several inhibiting factors were identified, such as differences in family backgrounds, the influence of social environments and social media, and limited time allocation for PAI learning. Overall, the development of patience and forgiveness characters can be optimized through collaboration between teachers, schools, and families.